Physicochemical and geotechnical properties of an ash-slag mixture deposited on a landfill in terms of its use in engineering - Szwalec, Artur; Gruchot, Andrzej; Mundała, Paweł; Zawisza, Eugeniusz; Kędzior, Renata (Geology, Geophysics and Environment, 2018)
Coal combustion ash-slag mixtures have been deposited in landfills in Poland for decades. At the same time, there is a shortfall in the amount of available materials related to the construction and modernisation of transportation infrastructure. Thus, a typical landfill of a power station was chosen and the aim of the study was to assess the suitability of an ash-slag landfill mixture for construction engineering purposes. The following physicochemical analyses were conducted: pH, specific electrical conductivity and determination of the leachability of basic (Ca, Na, K and Mg) and trace elements (Cd, Pb, Cr, Zn and Cu). The content of selected basic and trace elements were determined in the eluates by FAAS and standard methods were applied for geotechnical analyses. The most likely conditions were assumed to the model. The mixture will not jeopardize surface water quality in terms of the concentrations of basic, hazardous or priority elements. The content of these elements also does not exceed permissible concentrations for groundwater. The conductance and pH of the eluates are in compliance with current laws. The solid mixture has favourable geotechnical parameters which are significantly dependent on moisture content. The slope stability calculations for embankments created from the mixture at optimum moisture content and high compaction (Is≥ 0.95) indicate that they will be stable even in the case of high gradients (1:1.5). The slopes will be unstable in conditions of submersion, which should not occur if we assume the embankment will be used for passive flood protection. The mixture is particularly suitable for the purposes of earth structures, provided that they are isolated from water.